1999
DOI: 10.1002/(sici)1097-0231(19990615)13:11<986::aid-rcm595>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Covalent chemical modification of self- assembled fluorocarbon monolayers by low- energy CH2Br2+· ions: a combined ion/surface scattering and X-ray photoelectron spectroscopic investigation

Abstract: , an indicator of terminal CF 3 to CF 2 Br conversion. X-ray photoelectron spectroscopy (XPS) was used to confirm the presence of organic bromine at the surface; Br ( 3 P 3/2 ) and Br ( 3 P 1/2 ) peaks were present at binding energies of 182 and 190 eV, respectively. XPS analysis also revealed increased surface modification at higher collision energies in these reactive ion bombardment experiments, as exemplified by the increased hydrocarbon/fluorocarbon peak ratio in the C(1s) region and incorporation of oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Surface modification using reactive landing of low-energy (o100 eV) ions has been reported by several groups. Examples include formation of silicon nitride by collisions of low-energy N + and N 2 + ions with a Si(100) surface, 53 formation of Si-O bond between the OH-terminated SAM (HO-SAM) surface and a variety of SiX + ions, [54][55][56] esterification and ether formation on the HO-SAM surface following collisions with C 6 H 5 CO + and C 6 H 5 CH 2 + ions, respectively, 57 chemical modification of FSAM [58][59][60][61] and polystyrene 62 surfaces, growth and modification of thin films, 2,63-65 and covalent immobilization of small molecules and proteins on plasma-treated metal surfaces. 26,28 Peptide-modified surfaces are commonly used in biological and medical applications ranging from characterization of molecular recognition events at the amino acid level and identification of biologically active motifs in proteins to the development of novel biosensors and substrates for improved cell adhesion.…”
Section: Covalent Immobilization Of Peptides Using Reactive Landingmentioning
confidence: 99%
“…Surface modification using reactive landing of low-energy (o100 eV) ions has been reported by several groups. Examples include formation of silicon nitride by collisions of low-energy N + and N 2 + ions with a Si(100) surface, 53 formation of Si-O bond between the OH-terminated SAM (HO-SAM) surface and a variety of SiX + ions, [54][55][56] esterification and ether formation on the HO-SAM surface following collisions with C 6 H 5 CO + and C 6 H 5 CH 2 + ions, respectively, 57 chemical modification of FSAM [58][59][60][61] and polystyrene 62 surfaces, growth and modification of thin films, 2,63-65 and covalent immobilization of small molecules and proteins on plasma-treated metal surfaces. 26,28 Peptide-modified surfaces are commonly used in biological and medical applications ranging from characterization of molecular recognition events at the amino acid level and identification of biologically active motifs in proteins to the development of novel biosensors and substrates for improved cell adhesion.…”
Section: Covalent Immobilization Of Peptides Using Reactive Landingmentioning
confidence: 99%
“…Scattered and sputtered ion data have been used to show that various polyatomic ions will ''soft land'' as intact species upon FC surfaces at ϳ10 eV collision energies 17 and induce other types of covalent surface modification above 20 eV. 77 However, selective ionization effects prevent quantification of surface chemistry from scattered or sputtered ions, thereby complicating comparison with our results. Finally, Ͻ100 eV ion-surface scattering tends to sample the repulsive wall of the ion-surface scattering potential, thereby emphasizing mechanical effects of the collision while suppressing chemical effects that occur on the attractive portion of the potential.…”
Section: Energy Transfer In Ion-surface Collisionsmentioning
confidence: 99%
“…It was further demonstrated that these ion–surface reactions chemically altered the surface molecular groups. For example, a transhalogenation reaction, performed with reagents such as PCl 3 + or Si(NCO) + , has been shown to transform fluorocarbon surfaces chemically into terminal CF 2 X units, where X represents the halogen atom or pseudohalogen in the projectile ion 32–34. The scattered ion beam then includes such reaction products as PCl 2 F + .…”
Section: Introductionmentioning
confidence: 99%